THE EFFECT OF RELIGIOSITY ON CUSTOMER DECISIONS IN CHOOSING ISLAMIC BANKS WITH ATTITUDES AND TRUST AS INTERVENING VARIABLES IN LHOKSEUMAWE CITY - Puteh, Anwar; Sukiman, Sukiman; Yafiz, Muhammad (CV. Radja Publika, 2021)
The religious phenomenon of the study is fascinating to study and is associated with the concept of community behavior as consumers of a sharia-based product. Research on Studies that include the relationship between religious behavior and consumer behavior in decision-making on a product is microscale, so it attracts the interest of researchers. Religisutias is a state of understanding, obedience, a person believing in a religion embodied in the experience of values, and action under the teachings of faith in taking a favorable decision. The role of religiosity with customer attitudes and trust and its relevance to customer decisions in choosing a sharia bank. This study aims to analyze the relationship of religiosity to customer decisions in selecting a sharia bank, either directly or mediated by the variables of attitudes and trust. The conducted research n Lhokseumawe City. The collected data through a questionnaire distributed to 200 respondents. The data is processed by Path Analysis using the SEM program. The results prove that direct testing is obtained that (a) religiosity has a positive and significant effect on the attitudes of Islamic bank customers, and (b) has a positive effect on the trust of Islamic bank customers. (c) Influencing customers in choosing Islamic banks. (d) Attitudes influence customer decisions (e) trust affects the customer's decision in choosing an Islamic bank. Indirect testing (path) shows (f) religiosity also influences customer decisions in choosing Islamic banks through attitude as an intervening variable. (g) Influence on customer decisions in determining Islamic banks through trust as an intervening variable. The results strengthened Kinsmen's behavioral theory and previous empirical findings that religiosity is an essential predictor of consumer behavior, especially decision-making. A person's attitudes and trusts based on religious values that he trusts are predictors that direct his behavior to purchase a product. The benefits of this study can recommend that Islamic banking needs to provide services and provide superior products. Improving service quality such as contracts under sharia will affect customer attitudes and behavior and are expected to maintain customer consistency to be loyal in using sharia bank services. attitudes and trusts based on religious values that he trusts are predictors that direct his behavior to purchase a product. The benefits of this study can recommend that Islamic banking needs to provide services and provide superior products. Improving service quality such as contracts under sharia will affect customer attitudes and behavior and are expected to maintain customer consistency to be loyal in using sharia bank services. attitudes and trusts based on religious values that he trusts are predictors that direct his behavior to purchase a product. The benefits of this study can recommend that Islamic banking needs to provide services and provide superior products. Improving service quality such as contracts under sharia will affect customer attitudes and behavior and are expected to maintain customer consistency to be loyal in using sharia bank services.